Assessing the Legal Personality of Sexbots in the Light of Human Rights - Gupta, Arushi (Kathmandu School of Law Review, 2020)
Sexbots have been the subject of much prurient curiosity for all of the adult population. The scepticism about the extent of human interaction in the future has created ambiguity about the prospects of the flesh trade industry all over the world. The evolution of sexbots from animatronic models to sentient beings capable of decision-making ability would pose a fundamental question about their impact on human rights and the obstacles it would create for the people employed in this sector. The ethico-legal constraints about their replacements as sex workers for utilitarian purposes evaluate the boundaries of acceptable sexual practices. With the advent of artificial intelligence in robotics, these customizable simulacra capable of human affection explore the pragmatic question of their legal personality. This paper analyzes the intersectionality of artificial intelligence and robotics in the light of ethical limits and legal implications on human rights. It imposes a duty on humans to address the permissible limits of customizability and the sufficiency of the existing legal framework to minimize the sufferings of these sentient beings. The complexities involved in the controversial facet of human-robot relationship entail us to gauge upon the jurisprudential aspects of the rights and legal personality of these robots.